Isolation and Identification of Phosphate Solubilizing Bacteria from The Rhizosphere of Dry Land Lamtoro Plants (Leucaena leucocephala) in North and South Lombok Regions - Hartanto, Priyo; Zulkifli, Lalu; Karnan; Sedijani, Prapti; Mahrus (Jurnal Biologi Tropis, 2023)
Phosphate solubilizing rhizobacteria are microorganisms that live in the rhizosphere of plants and have the ability to increase the availability of phosphate in the soil, thereby reducing dependence on chemical fertilizers which are harmful to the environment. This research aims to isolate rhizosphere bacteria from Lamtoro plants and test their ability to dissolve phosphate. Screening the ability of these bacterial isolates was carried out using Pikovskaya media and quantitatively using a spectrophotometer. The test results showed that there were 3 isolates, namely KLU13, A2 and KLS1, which had IKF values in the medium category. Meanwhile, the other 4 isolates had abilities in the low category (isolates A1, A31BK, A3BB and A3). The results of quantitative tests with a spectrophotometer showed that there was an increase in dissolved phosphate from day 2 to day 6. Isolates KLU13, A3 and KLS1 dissolved the highest phosphate on day 6 with values of 14.65 ppm, 14.81 ppm and 10.32 ppm respectively. It can be concluded that the isolate obtained from the Lamtoro rhizosphere which grows in the dry areas of Lombok Island has the potential to be developed as a biofertilizer in the future.